Prenatal Diagnosis of Fetal Inguinoscrotal Hernia: A Case Report and Review of the Literature - Özçimen, Emel Ebru; Özçimen, Necati; Gürbüz, Ali Sami; Akkoyun, İbrahim (Gynecology Obstetrics & Reproductive Medicine, 2010)
Fetal inguinal hernia is rarely diagnosed antenatally. Here we reported a case of prenatal diagnosis of a inguinoscrotal hernia at 35 weeks’ gestation and was discussed in the light of literature.